2007
DOI: 10.1086/520937
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antipneumococcal Antibodies and Pneumococcal Colonization in Adults with Chronic Obstructive Pulmonary Disease

Abstract: Antibodies to pneumococcus are thought to represent the primary mechanism of naturally acquired resistance to colonization. Here, however, we show that, in patients with chronic obstructive pulmonary disease (COPD), resistance to pneumococcal colonization is not associated with higher concentrations of serum anti-capsular or -noncapsular antibodies. We compared preacquisition serum antibody concentrations to capsular antigens 6B, 7F, 14, 19F, and 23F from patients with COPD who did and did not acquire pneumoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
0
21
1
Order By: Relevance
“…Similar patterns have been suggested for nasopharyngeal carriage (8). Experimental (20,21) and observational (7,16) studies in adults have found little or no evidence that higher anticapsular antibody concentrations are associated with greater protection from colonization.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Similar patterns have been suggested for nasopharyngeal carriage (8). Experimental (20,21) and observational (7,16) studies in adults have found little or no evidence that higher anticapsular antibody concentrations are associated with greater protection from colonization.…”
mentioning
confidence: 54%
“…Interestingly, there was also significant up-regulation of IL-17 expression (27). In a study of elderly adults with chronic obstructive pulmonary disease, we have shown that systemic antipneumococcal antibodies did not predict resistance to the acquisition of a new pneumococcal strain, suggesting that other mechanisms, possibly including T cells, may be responsible (16). In a recent study, significantly lower proliferative and cytokine peripheral blood T-cell responses to pneumolysin were observed in children who were colonized with S. pneumoniae than in noncolonized children, raising the intriguing hypothesis that T-cell responses to this antigen may be associated with increased resistance to pneumococcal colonization (35).…”
Section: Discussionmentioning
confidence: 90%
“…A recent study also reported that higher levels of antipneumococcal antibodies did not correlate with protection from pneumococcal colonization in patients with COPD [35]. Therefore, the question arises as to why an additional increase of IgG in sera is required for preventing infectious acute exacerbation in COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…First, although the greater immunogenicity of PCV7 may provide improved protection against invasive pneumococcal disease and pneumonia, it is not clear that the vaccine will prevent acute exacerbations of COPD. Prior studies have shown that patients with COPD are frequently colonized with S pneumoniae and that this colonization is a predictor of subsequent exacerbation, but higher levels of anti-pneumococcal IgG and OPK have not been associated with bacterial clearance (25). It is possible that protein-conjugate vaccines may elicit greater IgA antibody responses as compared with polysaccharide vaccines and this may augment the mucosal immune response and better protect against both colonization and exacerbation (26).…”
Section: Discussionmentioning
confidence: 99%